2019
DOI: 10.2196/14797
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Scribes on Patient-Physician Communication in Primary Care Encounters: Mixed Methods Study

Abstract: Background With the increasing adoption of electronic health record (EHR) systems, documentation-related burdens have been increasing for health care providers. Recent estimates indicate that primary care providers spend about one-half of their workdays interacting with the EHR, of which about half is focused on clerical tasks. To reduce documentation burdens associated with the EHR, health care systems and physician practices are increasingly implementing medical scribes to assist providers with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
(24 reference statements)
0
12
0
Order By: Relevance
“…Five studies were randomized controlled trials, [15][16][17][18][19] 23 studies were prospective nonrandomized studies, 10 studies were retrospective, [43][44][45][46][47][48][49][50][51][52] and 1 study had both prospective and retrospective components. 53 All studies were published between 2010 and 2020. Most studies were conducted in the United States, [15][16][17][18]21,23,24,[26][27][28][29][30][32][33][34][35][36][37][38][39][40][41][43][44][45][46][47][48][49][50][51][52][53] with ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies were randomized controlled trials, [15][16][17][18][19] 23 studies were prospective nonrandomized studies, 10 studies were retrospective, [43][44][45][46][47][48][49][50][51][52] and 1 study had both prospective and retrospective components. 53 All studies were published between 2010 and 2020. Most studies were conducted in the United States, [15][16][17][18]21,23,24,[26][27][28][29][30][32][33][34][35][36][37][38][39][40][41][43][44][45][46][47][48][49][50][51][52][53] with ...…”
Section: Resultsmentioning
confidence: 99%
“…Most studies were conducted in the United States, [15][16][17][18]21,23,24,[26][27][28][29][30][32][33][34][35][36][37][38][39][40][41][43][44][45][46][47][48][49][50][51][52][53] with 4 conducted in Australia 19,22,25,42 and 2 performed in Canada. 20,31 Nineteen studies were conducted in EDs, 17,19,20,[22][23][24][25][26][27]31,36,38,[42]<...>…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…42 Furthermore, the use of scribes does not decrease patient satisfaction. 43 One recent study found that the use of scribes in primary care increased the number and intensity of patients seen per hour, increased patient-facing time, increased total physician-patient interaction time, decreased the time physicians spent interacting with a computer, and decreased the after-hours time spent in EMR documentation. 44 Other physician-driven changes in EMR processes may improve usability, patient safety, and physician job satisfaction, and decrease physician burnout.…”
Section: Clinical Significancementioning
confidence: 99%
“… 3 , 6–10 , 14 , 16 Since their review included only papers published through 2017 and a good deal of research has been done since then, we updated their literature search, finding additional relevant papers with results similar to those in prior studies: The increase in provider satisfaction and productivity has been further verified. 17–28 In addition, studies of scribes have found other positive outcomes, such as increasing the joy of practicing. 24 It is therefore reasonable, after reviewing these studies, to conclude that the use of medical scribes can have a positive impact on provider workflow, provider and patient satisfaction, and on organizational finances.…”
Section: Introductionmentioning
confidence: 99%